"Si fier tornei": Benoîts ,Roman de Troie' und die höfische Kultur des 12. Jahrhunderts - Malatrait, Solveig Kristina (Hamburg University Press, 2011)
The representation of Troy is a natural part of the scholarly knowledge in the 12th century which is characterized by worship, but also by the acquisition of antiquity. Benoît de Sainte-Maure's "Roman de Troie" received a wide and intense contemporary reception. In 1870/71, Aristide Joly provided a first critical scientific appraisal of the "Roman de Troie", and after almost 140 years, Solveig Malatrait now presents a monograph that reconsiders the masterpiece of the Old French epic from a cultural studies perspective.